The Policy and Practice of Microcredit in Rural China: Toward a Relational Understanding of Heterogeneous Implementation. (July 2018) - Loubere, Nicholas; Shen, Qiu
Much research on rural development interventions in China has found substantial variation in their implementation at the local level. These studies often analyze the reasons for this heterogeneity by identifying variables responsible for influencing (or distorting) interventions as they travel from central formulation to local implementation. Through an in-depth ethnographic examination of the local implementation of one of China's largest microcredit programs in three townships in rural Jiangxi province, this article challenges the dominant depiction of external development interventions as reified and linear, and instead proposes a relational approach to understanding local heterogeneity. This approach reveals implementation outcomes to be emergent from negotiations between diverse sets of actors at different levels. At the same time, it becomes clear that microcredit implementation reflects the contradictions implicit in China's political economy of development. This points to two levels of implementation "relationality, " which results in unpredictable semi-chaotic variation, while simultaneously reproducing wider developmental relations.